Thermal Performance Enhancement of Serpentine Cooling Design Using Branch Modification for Lithium-Ion Batteries - Arya Rafi Abrari; Teguh Hady Ariwibowo; Dadet Pramadihanto; Nu Rhahida Arini; Eko Henfri Binugroho; Akio Miyara (Automotive Experiences, 2024)
Lithium iron phosphate (LiFePO4) batteries offer advantages such as low cost, safety, environmental compatibility, and stability over repeated cycles. However, when subjected to high currents, this battery generates thermal issues, particularly when arranged in packs. This study aims to maintain the LiFePO4 80Ah battery within an optimal temperature range (20 Â°C ”“ 40 Â°C) while minimizing pumping power. The proposed research introduces a serpentine channel with additional branches. The design variations include a gradient in branch spacing and changes in channel width. Each design is evaluated using dimensionless parameters representing maximum temperature, temperature uniformity, pumping power, and cooling efficiency coefficient. The best design from each variation is then compared with the conventional serpentine (CS) channel design, which is well-known for its superior thermal performance. The gradient variation reduces ð‘‡ð‘šð‘Žð‘¥âˆ— and ð‘‡ðœŽ by 0.07 and by 0.42, respectively, compared to the non-gradient channel design, at a Re 400 and a C-rate 3 C. The design with the largest channel width reduces ð‘‡ð‘šð‘Žð‘¥âˆ— by 0.57 or 11.32 Â°C compared to the design with the smallest channel width. At a Re 1000 and C-rate 3 C, the reduction in ð‘‡ð‘šð‘Žð‘¥âˆ— for the proposed channel design compared to the CS design is 0.017. In terms of the friction factor (ð‘“), the proposed design is 0.0149 lower than the CS design. The results indicate that the thermal performance of the proposed channel design is better than that of the CS design, with reduced pumping power.